Development of organ‐specific autoimmunity by dysregulated Aire expression. Issue 5 (9th April 2022) - Nishijima, Hitoshi; Sugita, Mizuki; Umezawa, Natsuka; Kimura, Naoki; Sasaki, Hirokazu; Kawano, Hiroshi; Nishioka, Yasuhiko; Matsumoto, Minoru; Oya, Takeshi; Tsuneyama, Koichi; Morimoto, Junko; Matsumoto, Mitsuru
Abstract: Deficiency for AIRE/Aire in both humans and mice results in the development of organ‐specific autoimmune disease. We tested whether augmented and/or dysregulated AIRE/Aire expression might be also prone to the breakdown of self‐tolerance. To define the effect of augmented Aire expression on the development of autoimmunity, antigen‐specific clonal deletion and production of clonotypic regulatory T cells (Tregs) in the thymus were examined using mice expressing two additional copies of Aire in a heterozygous state (3xAire‐knockin mice: 3xAire‐KI). We found that both clonal deletion of autoreactive T cells and production of clonotypic Tregs in the thymus from 3xAire‐KI were impaired in a T‐cell receptor‐transgenic system. Furthermore, 3xAire‐KI females showed higher scores of experimental autoimmune encephalomyelitis induced by myelin oligodendrocyte glycoprotein than wild‐type littermates, suggesting that augmented Aire expression exacerbates organ‐specific autoimmunity under disease‐prone conditions. In humans, we found that one patient with amyopathic dermatomyositis showed CD3 – CD19 – cells expressing AIRE in the peripheral blood before the treatment but not during the remission phase treated with immunosuppressive drugs. Thus, not only loss of function of AIRE/Aire but also augmented and/or dysregulated expression of AIRE/Aire should be considered for the pathogenesis of organ‐specific autoimmunity. We suggest that further analyses should be pursued to establish a novel link between organ‐specific autoimmune disease and dysregulated AIRE expression in clinical settings. Abstract : Mice expressing augmented Aire from authentic Aire‐expressing cells showed higher experimental autoimmune encephalomyelitis scores than wild‐type littermates, suggesting that augmented Aire expression exacerbates organ‐specific autoimmunity. This was associated with the defect in the antigen‐specific clonal deletion and production of clonotypic regulatory T cells in the thymus. Interestingly, one patient with amyopathic dermatomyositis showed CD3 – CD19 – cells expressing AIRE in the peripheral blood before the treatment but not during the remission phase, suggesting a novel link between organ‐specific autoimmunity and dysregulated AIRE expression also in clinical settings.